Vulvar soft tissue tumors. Issue 1 (1st January 2004) - Behranwala, K. A.; Latifaj, B.; Blake, P.; Barton, D. P. J.; Shepherd, J. H.; Thomas, J. M.
Abstract : Objective: To report our incidence of soft tissue tumors at this site and to discuss various prognostic factors. Methods: All patients with a diagnosis of vulvar soft tissue neoplasms were studied from a prospective database at the Royal Marsden Hospital between January 1985 and July 2001. Results: Seventeen vulvar soft tissue neoplasms (11 malignant and six benign) were treated during this period. Leiomyosarcoma ( n = 5) and aggressive angiomyxoma ( n = 4) were the most frequent histologic types. According to the grade, there were four G3, three G2, three G1 and could not be assessed in one patient. Local recurrence occurred in six patients with sarcoma (three with high grade and one each with intermediate, low, and undetermined grade). In this group, five patients had negative microscopic margins and one patient had positive microscopic margins on excision. All three women with low-grade sarcomas are alive without evidence of disease. Three patients with aggressive angiomyxoma also had a local recurrence. Conclusion: Surgical excision is the primary treatment where possible. The grade of the tumor is an important predictor for local recurrence and outcome. Aggressive angiomyxoma is a local problem. Leiomyosarcoma and aggressive angiomyxoma are the most frequent histologic types.